Designing a STEAM-infused project-based learning framework to foster mathematics students’ critical and creative thinking - Ikhlas, Al; Syaiful; Huda, Nizlel; Zurweni (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to design and implement a STEAM-infused Project-Based Learning framework to strengthen mathematics students’ critical and creative thinking through interdisciplinary and contextual learning experiences. Method: A design-based research approach employing the ADDIE model was used with undergraduate mathematics students at STKIP Muhammadiyah Sungai Penuh. Data were collected through pre-tests, post-tests, expert validation, classroom observations, and reflective journals, and analyzed quantitatively using normalized gain calculations and qualitatively through thematic interpretation. Findings: Results indicate substantial improvement in higher-order thinking, with normalized gains of 0.61 for critical thinking and 0.55 for creative thinking. Expert evaluations confirmed the framework’s validity, practicality, and relevance, while qualitative data revealed increased engagement, collaboration, and contextual understanding during project implementation. Significance: The STEAM-infused Project-Based Learning framework offers an effective and innovative approach to nurturing students’ critical and creative reasoning by connecting mathematical concepts to real-life contexts. The model provides a practical pathway for advancing 21st-century mathematics education in higher education institutions